Circulating Immunosuppressive Regulatory T Cells Predict Risk of Incident Cutaneous Squamous Cell Carcinoma - Rollison, Dana E.; Messina, Jane L.; Cherpelis, Basil S.; Fenske, Neil A.; Schell, Michael J.; Adeegbe, Dennis O.; Zhao, Yayi; Amorrortu, Rossybelle P.; Akuffo, Afua A.; Hesterberg, Rebecca S.; Epling-Burnette, Pearlie K. (Frontiers in Medicine, 2021)
Ultraviolet radiation exposure (UVR) is a risk factor for cutaneous squamous cell carcinoma (cuSCC) and has been shown to be positively associated with circulating immunosuppressive regulatory T cells (“Tregs”). However, the risk of cuSCC in association with circulating Tregs has not been studied. The aim of this study was to determine whether circulating Treg levels are associated with cuSCC development, particularly in the context of high UVR. Blood and spectrophotometer-based UVR measurements were obtained on 327 immunocompetent individuals undergoing routine skin cancer screenings at baseline and followed for up to four years for incident cuSCC development within a prospective cohort study. Proportions of phenotypically distinct Tregs, especially CCR4hi and CLA+ cells which are associated with activation and homing, respectively were measured by flow cytometry. Tregs in cuSCC tumors were assessed using immunohistochemistry and graded for solar elastosis, a measure of cumulative UVR damage. Of several Treg phenotypes examined, higher levels of circulating CCR4hi Tregs at baseline were significantly associated with increased risk of subsequent cuSCC; those with higher levels of both CCR4hi and UVR were four times more likely to develop cuSCC compared to those with lower levels of both (Hazard Ratio=4.11, 95% CI= 1.22-13.90). Within cuSCC tumors, CCR4hi Tregs were positively associated with solar elastosis. Results show that a higher proportion of CCR4hi peripheral Tregs predicts incident cuSCC up to four years, especially among highly UV-exposed individuals. Research of the underpinning biology of Tregs in UVR-associated skin damage may possibly reveal novel opportunities for screening, prevention, and treatment.